Hubungan Pengetahuan dan Sikap Ibu Serta Dukungan Keluarga Terhadap Pemberian ASI Eksklusif Di Wilayah Kerja Puskesmas Kemiling - Fina Handayani; Nurul Aryastuti; Fitri Eka Sari; Dhiny Easter Yanti (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2026)
Less than half of infants under 6 months of age receive exclusive breastfeeding. Indonesia's exclusive breastfeeding coverage in 2022 was recorded at only 67.96%, down from 69.7% in 2021. The average length of time a child is breastfed in Lampung Province is 11.35 months. This shows that on average, infants in Lampung Province have received breast milk for more than 6 months but not reaching 24 months. The purpose of the study was to determine the relationship between maternal knowledge and maternal attitudes and family support with exclusive breastfeeding in the Kemiling Health Center Work Area. This study is a quantitative study with a Cross Sectional design. The population is all mothers who have toddlers in the Kemiling Health Center Work Area totaling 648 respondents and a sample of 97 respondents using a purposive sampling technique with a questionnaire sheet. The study was conducted in the Kemiling Health Center Work Area and was conducted in August-October 2024. Data analysis used univariate analysis and bivariate analysis. The results of the study showed that 54 people (55.7%) gave exclusive breastfeeding and 43 people (44.3%) did not give exclusive breastfeeding, 47 people (48.5%) had poor knowledge and 50 people (51.5%) had good knowledge, 44 people (45.4%) had negative attitudes and 53 people (54.6%), 66 people (68.0%) had positive family support and 31 people (32.0%) did not have family support. There was a significant relationship between maternal knowledge (p-value 0.021) and maternal attitude (p-value) and there was no relationship between family support (p-value 1.000) and exclusive breastfeeding at the Kemiling Health Center, Bandar Lampung.